Composite current collector and preparation method thereof, and negative electrode-free sodium metal battery

CN122907644APending Publication Date: 2026-10-13FUYANG SOLID STATE ENERGY STORAGE TECH LIYANG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610950687.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-29
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

[0020]本发明的有益效果是,本发明设计合理,具有以下优点:本发明通过亲钠金属层来调制钠离子的均匀沉积,抑制钠枝晶的产生,同时表面的金属氧化物保护层能够与钠离子发生原位反应,生成无机的Na2O产物,Na2O能够参与SEI的形成,提升SEI的稳定性,从而进一步促进钠离子的均匀沉积,同时抑制界面副反应,有效保护了亲钠金属层,极大地延长了亲钠金属层的使用寿命,延缓其因剧烈的体积膨胀和收缩而导致的粉碎和失活。利用本发明所制备的无负极钠金属电池具有更高的放电比容量、更好的循环稳定性和更长的循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907644A_ABST
    Figure CN122907644A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of sodium metal battery, and especially to a composite current collector, a preparation method thereof and a negative-electrode-free sodium metal battery. The composite current collector is sequentially provided with a current collector substrate layer, a sodium metal-philic layer and a metal oxide protective layer from bottom to top; the sodium metal-philic layer has a general formula of M, and the metal oxide protective layer has a general formula of M x O y ; M is one of gold, silver, zinc, tin, antimony, bismuth, indium, magnesium and calcium. The present application discards the traditional single sodium metal-philic layer method, generates Na2O by in-situ reaction of the metal oxide protective layer and sodium ions, participates in SEI formation, improves the stability of SEI, further promotes the uniform deposition / detachment behavior of sodium ions, inhibits the growth of sodium dendrites and interface side reactions, prolongs the service life of the sodium metal-philic layer, and significantly improves the discharge specific capacity, cycle stability and cycle life of the negative-electrode-free sodium metal battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sodium metal battery technology, and in particular to a composite current collector and its preparation method, and a negative electrode-free sodium metal battery. Background Technology

[0002] Currently, with the strategic shift in the global energy landscape from fossil fuels to renewable energy sources such as wind and solar power, the demand for efficient and low-cost electrochemical energy storage technologies is becoming increasingly urgent. Lithium-ion batteries have achieved great success in consumer electronics and electric vehicles due to their high energy density. However, lithium resources are only about 0.0065% abundant in the Earth's crust and are extremely unevenly distributed, making it difficult to meet the cost and resource sustainability requirements of future grid-scale energy storage. In contrast, sodium resources are about 1000 times more abundant in the Earth's crust, widely distributed, and have an overwhelming cost advantage. Therefore, sodium-ion batteries are widely considered an ideal candidate for next-generation large-scale energy storage systems.

[0003] Traditional sodium-ion batteries are limited by the specific capacity of the intercalation-type anode material, and their energy density is typically below 160 Wh kg. -1 It is difficult to match lithium-ion batteries. Using metallic sodium as the negative electrode, it boasts a capacity of 1166 mAh g⁻¹. -1 The high theoretical specific capacity and low redox potential of -2.71 V are effective ways to improve the energy density of sodium-based batteries. However, traditional sodium metal batteries have significant safety hazards and manufacturing challenges. Sodium metal is chemically reactive and readily reacts with the electrolyte, leading to uncontrolled sodium dendrite growth, continuous electrolyte consumption, and the formation of an unstable SEI, which in turn causes low coulombic efficiency, short cycle life, and potential safety risks. Simultaneously, the presence of excess sodium metal on the negative electrode side also reduces the battery's mass and volumetric energy density.

[0004] In recent years, the anode-free sodium metal battery, as a novel battery configuration, has shown significant advantages in maximizing energy density, simplifying manufacturing processes, reducing production costs, and improving safety by completely eliminating the active material on the negative electrode side and relying solely on the reversible electrochemical deposition / stripping of sodium ions provided by the positive electrode on the current collector to construct a dynamic sodium metal anode. However, in anode-free sodium metal batteries, since there is no initial sodium metal on the negative electrode side and the positive electrode is the only active sodium source, the irreversible consumption of the sodium source during charging and discharging directly leads to rapid performance degradation. Specifically, anode-free sodium metal batteries face three core challenges: First, sodium metal has extremely strong reducing properties, easily causing side reactions in the electrolyte that consume the limited active sodium, and the unstable SEI film further exacerbates the irreversible loss of active sodium through repeated rupture and reconstruction. Second, coulombic efficiency, as a key parameter directly determining the cycle life of anode-free sodium metal battery, is particularly important in systems where there is no excess sodium to replenish. Secondly, heterogeneous nucleation of sodium on the current collector surface requires overcoming a high nucleation barrier. Traditional current collectors such as aluminum and copper foils have low binding energy with sodium, and the uneven distribution of nucleation sites on the surface leads to uneven sodium ion flux, thereby exacerbating dendrite growth and the accumulation of "dead sodium." Thirdly, due to the lack of pre-stored metallic sodium, sodium deposition / stripping is accompanied by unrestricted volume changes and huge internal stress changes, which can severely deteriorate interfacial contact and even damage the stability of the battery structure. Therefore, how to improve the reversibility and uniformity of sodium deposition / stripping under limited sodium source conditions is a key scientific problem for achieving long-term cycle stability in anode-free sodium metal batteries.

[0005] To address these challenges, researchers have conducted extensive work and made significant progress in electrolyte design, current collector modification, and optimization of testing conditions. Constructing a sodium-affinity interface layer on the current collector surface has proven to be an effective strategy for regulating the uniform deposition of sodium ions. Studies have shown that introducing metals or alloys with sodium-affinity properties can significantly reduce the sodium nucleation overpotential and promote uniform sodium deposition. For example, metals such as Zn, Sn, Sb, Bi, and Au, and their alloys with sodium, have been proven to have good sodium-affinity properties, providing uniform nucleation sites. However, the sodium-affinity layer design strategy widely used in current research has a fundamental flaw: these sodium-affinity coatings are not fully sodium-bound. During the first charge cycle, they consume some active sodium ions from the positive electrode to form alloys or undergo interfacial reactions. As cycling continues, the sodium-affinity layer fractures and pulverizes due to repeated expansion and contraction, eventually becoming inactive or even peeling off from the current collector surface, exposing the underlying non-sodium-affinity substrate, and ultimately losing its function in regulating the uniform deposition of sodium ions.

[0006] Therefore, developing a novel composite current collector that not only has high sodium affinity but also has a sodium-loving metal layer that is not easily pulverized and deactivated is a key breakthrough to solve the current technical bottleneck of anode-free sodium metal batteries. It is urgent to develop a novel composite current collector with high discharge specific capacity, strong cycle stability, and long cycle life, as well as anode-free sodium metal batteries. Summary of the Invention

[0007] The technical problem this invention aims to solve is to overcome the shortcomings of existing technologies and provide a composite current collector and its preparation method, as well as a negative electrode-free sodium metal battery. The composite current collector of this invention not only promotes uniform sodium ion deposition and inhibits sodium dendrite growth through a sodium-loving metal layer, but also generates Na₂O through an in-situ reaction between the metal oxide protective layer and sodium ions, thereby improving SEI stability, suppressing interfacial side reactions, extending the lifespan of the sodium-loving metal layer, and enhancing the discharge specific capacity, cycle stability, and cycle life of the negative electrode-free sodium metal battery.

[0008] The technical solution adopted by the present invention to solve its technical problem is: a composite current collector, which is provided with a current collector base layer, a sodium-loving metal layer and a metal oxide protective layer from bottom to top; The current collector substrate layer is made of at least one of copper foil, copper foam, carbon-coated copper foil, nickel foam, aluminum foil, aluminum foam, and carbon-coated aluminum foil, and the thickness of the current collector substrate layer is 1 nm to 1 cm. The sodium-loving metal layer is generally denoted by formula M, and the metal oxide protective layer is generally denoted by formula M. x O y M is one of the following: gold, silver, zinc, tin, antimony, bismuth, indium, magnesium, and calcium.

[0009] A method for preparing the composite current collector as described above specifically includes the following steps: Step S1: Deposit a sodium-loving metal layer on the current collector substrate; Step S2: Deposit a metal oxide protective layer on the sodium-loving metal layer.

[0010] Further, in step S1, the deposition method of the sodium-loving metal layer is one or more of the following: direct coating, dry rolling, radio frequency magnetron sputtering, pulsed laser deposition, electron beam evaporation, molecular beam epitaxy, cluster beam deposition, evaporation deposition, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and plasma-enhanced physical vapor / chemical vapor / atomic layer deposition.

[0011] Furthermore, the deposition method of the sodium-loving metal layer specifically includes: using radio frequency magnetron sputtering, with a metal M target as the precursor; a high-purity argon atmosphere; and a vacuum degree of 1×10⁻⁶. -2 ~1×10 -3Pa; operating environment dew point is -60 ℃ to -30 ℃; deposition rate is 0.01 nm to 1 μm per minute; thickness of sodium-loving metal layer is 1 nm to 10 μm.

[0012] Preferably, in the method for depositing the sodium-loving metal layer, the argon gas purity is greater than or equal to 99.9%, and the vacuum degree is 2 × 10⁻⁶. -3 Pa, the operating environment dew point is -40 ℃, the deposition rate is 1 to 5 nm per minute, and the thickness of the prepared sodium-loving metal layer is 100 to 500 nm.

[0013] Furthermore, in step S2, the deposition method of the metal oxide protective layer is one or more of the following: radio frequency magnetron sputtering, pulsed laser deposition, electron beam evaporation, molecular beam epitaxy, cluster beam deposition, evaporation deposition, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and plasma-enhanced physical vapor / chemical vapor / atomic layer deposition.

[0014] Furthermore, the deposition method of the metal oxide protective layer specifically includes: using radio frequency magnetron sputtering, with a metal M target as the precursor; a mixed atmosphere of argon and oxygen, where the mass percentage of oxygen is 10%–90%; and a vacuum degree of 1×10⁻⁶. -2 ~1×10 -3 Pa; operating environment dew point is -60 ℃ to -30 ℃; deposition rate is 0.01 nm to 1 μm per minute; thickness of metal oxide protective layer is 1 nm to 10 μm.

[0015] Preferably, in the method for depositing the metal oxide protective layer, the flow rate ratio of oxygen to argon is 1:1, the purity of both oxygen and argon is greater than or equal to 99.9%, and the vacuum degree is 2 × 10⁻⁶. -3 Pa, the operating environment dew point is -40 ℃, the deposition rate is 1 ~ 5 nm per minute, and the thickness of the prepared metal oxide protective layer is 10 ~ 100 nm.

[0016] A sodium metal battery without a negative electrode includes a positive electrode, a sodium battery electrolyte, a separator, and the aforementioned composite current collector.

[0017] Furthermore, the positive electrode includes a current collector and a positive electrode slurry disposed on the current collector, the positive electrode slurry containing a positive electrode material.

[0018] Furthermore, the current collector is made of copper foil or aluminum foil; the positive electrode material is at least one of positive electrode active material and positive electrode active material containing element doping, and the positive electrode active material is one or more of transition metal oxides, polyanionic compounds, and Prussian blue analogues.

[0019] Furthermore, the transition metal oxide is P2-Na. x Ni x Mn 1-x O2, O3-NaFe 1-x Mn x At least one of O2; the polyanionic compound is Na3V2(PO4)3 or Na2FeP2O7; the Prussian blue analogue is at least one of Na2Mn[Fe(CN)6] or Na2Fe[Fe(CN)6]. Preferably, it is the positive electrode active material Na3V2(PO4)3.

[0020] The beneficial effects of this invention are as follows: This invention is rationally designed and has the following advantages: It modulates the uniform deposition of sodium ions through a sodium-loving metal layer, suppressing the formation of sodium dendrites. Simultaneously, the surface metal oxide protective layer can react in situ with sodium ions to generate inorganic Na₂O products. Na₂O can participate in the formation of the SEI (Sediment Injection Layer), improving its stability and further promoting the uniform deposition of sodium ions. At the same time, it suppresses interfacial side reactions, effectively protecting the sodium-loving metal layer and greatly extending its lifespan, delaying its pulverization and deactivation caused by drastic volume expansion and contraction. The anode-free sodium metal battery prepared using this invention has higher discharge specific capacity, better cycle stability, and longer cycle life. Attached Figure Description

[0021] The present invention will be further described below with reference to the accompanying drawings and embodiments.

[0022] Figure 1 The preparation process of Example 1 and surface SEM images and optical electron photographs of Comparative Examples 1, 2 and 1 at different magnifications are shown. Figure 2 These are XRD patterns of Comparative Example 1, Comparative Example 2, and Example 1; Figure 3 These are the surface SEM images and corresponding EDS distribution maps of Example 1; Figure 4 The first charge and discharge curves of the half-cells of Comparative Example 1, Comparative Example 2 and Example 1 are shown. Figure 5 This is an enlarged first-cycle sodium deposition overpotential diagram of the half-cells of Comparative Example 2 and Example 1; Figure 6 This is an enlarged voltage polarization diagram of the half-cell of Comparative Example 1, Comparative Example 2 and Example 1; Figure 7 The charging and discharging curves of the first, fifth, tenth, twentieth, thirtieth, fortyth, fiftyth, and sixtieth cycles of the comparative half-cell are shown. Figure 8The charging and discharging curves of the comparative half-cell for the 1st, 10th, 20th, 30th, 40th, 50th, 60th, 80th, 120th, 160th and 170th cycles are shown. Figure 9 The charging and discharging curves of the half-cell in Example 1 for the 1st, 50th, 100th, 200th, 300th, 400th and 500th cycles are shown. Figure 10 The long-cycle coulombic efficiency diagrams of the half-cells of Comparative Example 1, Comparative Example 2, and Example 1 are shown. Figure 11 The first charge and discharge curves of the full cells of Comparative Example 1, Comparative Example 2 and Example 1 are shown. Figure 12 This is a long-cycle curve graph of the full cells of Comparative Example 1, Comparative Example 2 and Example 1. Detailed Implementation

[0023] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, illustrating only the basic structure of the invention, and therefore only show the components relevant to the invention.

[0024] Example 1: This embodiment is an Al / Bi / Bi2O3 composite current collector. Preparation of the composite current collector: A 15 μm thick aluminum foil was used as the current collector substrate, and the surface was wiped clean with alcohol. A sodium-loving Bi layer and a Bi₂O₃ metal oxide protective layer were sequentially deposited on the aluminum foil surface using radio frequency magnetron sputtering. The precursor was a high-purity Bi target, and the vacuum degree was 2 × 10⁻⁶. -3 The operating environment had a dew point of -40 °C. When preparing the sodium-loving Bi layer, the sputtering atmosphere was high-purity argon, the film deposition rate was 1–5 nm per minute, and the thickness of the prepared sodium-loving Bi layer was 100–500 nm. When preparing the Bi₂O₃ metal oxide protective layer, the sputtering atmosphere was a mixture of oxygen and argon with a flow ratio of 1:1, the film deposition rate was 1–5 nm per minute, and the thickness of the prepared Bi₂O₃ metal oxide protective layer was 10–100 nm. The prepared composite current collectors were cut into discs with diameters of 16 mm and 19 mm and stored in an argon-filled glove box.

[0025] The current collector substrate used is aluminum foil. Sodium metal does not undergo an alloying reaction with aluminum foil, which is to improve the energy density of the battery.

[0026] The prepared sodium-loving metal Bi layer has a blackish-gray surface with no metallic luster, and is uniform and flat, and is stably and firmly bonded to the current collector substrate.

[0027] The prepared Bi₂O₃ metal oxide protective layer has an amorphous structure; it can be a continuous or discontinuous layer on the surface of the sodium-loving Bi layer; and it is porous or dense. The prepared Bi₂O₃ metal oxide protective layer is transparent and colorless or transparent light yellow, with a glossy, uniform, and smooth surface, and it bonds stably and firmly with the sodium-loving Bi layer.

[0028] Assembly of the half-cell: The half-cell uses a composite current collector as the positive electrode and a sodium metal sheet as the negative electrode. It uses a Celgard 2500 separator and a Whatman GF / A glass fiber separator. The electrolyte used is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0029] Electrochemical performance testing of the half-cell: The testing procedure for the half-cell was set as follows: constant current discharge followed by constant current charging. The constant current discharge current density was 0.5 mA·cm⁻¹. -2 The discharge capacity is 0.5 mAh·cm⁻¹. -2 The constant current charging current density is 0.5 mA·cm. -2 The charging cutoff voltage is 1V. The cycle count is set to 1000 revolutions.

[0030] Assembly of the full cell: The full cell uses a composite current collector as the negative electrode and sodium vanadium phosphate as the positive electrode. The content of active material in the positive electrode is 94%, and the areal density of the positive electrode plate is 20 mg·cm³. -2 The positive electrode has a diameter of 12 mm. A Celgard 2325 diaphragm is used, and the electrolyte is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0031] Electrochemical performance testing of the full cell: The testing procedure for the full cell was set as constant current charging followed by constant current discharging. The testing rate was 0.1 C, where 1 C = 110 mA·g. -1 The charge / discharge cutoff voltage range is 2.4–3.8V, and the cycle count is set to 60 cycles.

[0032] Comparative Example 1: The comparative example is an Al current collector. Preparation of Al current collector: Aluminum foil with a thickness of 15 μm was used as the current collector, and the surface was wiped clean with alcohol. The aluminum current collector was cut into circular pieces with diameters of 16 mm and 19 mm and stored in a glove box filled with argon gas.

[0033] Assembly of the half-cell: The half-cell uses an Al current collector as the positive electrode and a sodium metal sheet as the negative electrode. It uses a Celgard 2500 separator and a Whatman GF / A glass fiber separator. The electrolyte used is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0034] Electrochemical performance testing of the half-cell: The testing procedure for the half-cell was set as follows: constant current discharge followed by constant current charging. The constant current discharge current density was 0.5 mA·cm⁻¹. -2 The discharge capacity is 0.5 mAh·cm³. -2 The constant current charging current density is 0.5 mA·cm. -2 The charging cutoff voltage is 1V. The cycle count is set to 1000 revolutions.

[0035] Assembly of the full cell: The full cell uses an Al current collector as the negative electrode and a sodium vanadium phosphate positive electrode as the positive electrode. The content of the positive electrode active material is 94%, and the areal density of the positive electrode plate is 20 mg·cm³. -2 The positive electrode has a diameter of 12 mm. A Celgard 2325 diaphragm is used, and the electrolyte is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0036] Electrochemical performance testing of the full cell: The testing procedure for the full cell was set as constant current charging followed by constant current discharging. The testing rate was 0.1 C, where 1 C = 110 mA·g. -1 The charge / discharge cutoff voltage range is 2.4–3.8 V, and the cycle count is set to 60.

[0037] Comparative Example 2 The comparative example is an Al / Bi composite current collector. Preparation of Al / Bi composite current collector: A 15 μm thick aluminum foil was used as the current collector substrate, and the surface was wiped clean with alcohol. A sodium-philic Bi layer was deposited on the aluminum foil surface using radio frequency magnetron sputtering. The preparation method, conditions, and thickness of the sodium-philic Bi layer were the same as those in Example 1. The prepared Al / Bi composite current collector was cut into discs with diameters of 16 mm and 19 mm and stored in an argon-filled glove box.

[0038] Assembly of the half-cell: The half-cell uses a composite current collector as the positive electrode and a sodium metal sheet as the negative electrode. It uses a Celgard 2500 separator and a Whatman GF / A glass fiber separator. The electrolyte used is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0039] Electrochemical performance testing of the half-cell: The testing procedure for the half-cell was set as follows: constant current discharge followed by constant current charging. The constant current discharge current density was 0.5 mA·cm⁻¹. -2 The discharge capacity is 0.5 mAh·cm³. -2 The constant current charging current density is 0.5 mA·cm. -2 The charging cutoff voltage is 1V. The cycle count is set to 1000 revolutions.

[0040] Assembly of the full cell: The full cell uses a composite current collector as the negative electrode and sodium vanadium phosphate as the positive electrode. The content of active material in the positive electrode is 94%, and the areal density of the positive electrode plate is 20 mg·cm³. -2 The positive electrode has a diameter of 12 mm. A Celgard 2325 diaphragm is used, and the electrolyte is 0.1 M NaBF4 + 0.9 M NaPF6 / DIGLYME.

[0041] Electrochemical performance testing of the full cell: The testing procedure for the full cell was set as constant current charging followed by constant current discharging. The testing rate was 0.1 C, where 1 C = 110 mA·g. -1 The charge / discharge cutoff voltage range is 2.4–3.8 V, and the cycle count is set to 60.

[0042] The Al / Bi / Bi2O3 composite current collector (Example 1) not only modulates the uniform deposition of sodium ions and suppresses the formation of sodium dendrites through the sodium-loving Bi layer, but also allows the Bi2O3 metal oxide protective layer on its surface to react with sodium ions during the first discharge cycle of the half-cell, generating Na2O and Na3Bi. The generated Na3Bi undergoes a dealloying reaction during subsequent charging, generating Bi, which integrates into the sodium-loving Bi layer to participate in modulating the deposition / stripping behavior of sodium ions. Meanwhile, Na2O participates in the composition of the SEI, enhancing its stability and suppressing interfacial side reactions. This further promotes the uniform deposition of sodium ions while effectively protecting the sodium-loving Bi layer, preventing it from shattering and deactivating due to drastic volume expansion. Therefore, the current collector modification method proposed in this invention, combining a sodium-loving metal layer and a metal oxide protective layer, abandons the traditional method of selecting a single sodium-loving metal layer. It emphasizes the exploration of the mechanism and structural protection of the sodium-loving metal layer, significantly extending its lifespan. The constructed anode-free sodium metal battery achieves higher discharge specific capacity, better cycle stability, and longer cycle life.

[0043] Figure 1The preparation process of Example 1 and surface SEM images and optical electron photographs at different magnifications of Comparative Examples 1, 2, and 1 are shown. It is evident that the preparation method of the present invention is simple, quick, convenient, and widely applicable, and allows for flexible control of different film thicknesses. The film coating has a significant impact on the surface morphology of the Al current collector. The original Al current collector surface is relatively smooth. After being coated with a sodium-loving Bi layer, the Al / Bi composite current collector surface exhibits sparse, loose, and rough granular characteristics. Further coating with a Bi₂O₃ metal oxide protective layer increases the particle density on the Al / Bi / Bi₂O₃ composite current collector surface, resulting in a more uniform particle size distribution and a denser film morphology.

[0044] Figure 2 The XRD patterns of Comparative Example 1, Comparative Example 2, and Example 1 are shown. The XRD patterns of Comparative Example 1 and Comparative Example 2 verify the coverage of the sodium-loving Bi layer on the Al current collector surface, and the absence of other impurity peaks. No peaks of Bi₂O₃ metal oxide were found in the XRD pattern of Example 1, indicating that the Bi₂O₃ metal oxide protective layer has an amorphous structure and is relatively thin.

[0045] Figure 3 The surface SEM image and corresponding EDS distribution map of Example 1 are shown. The signals of Al, Bi, and O elements are visible, indicating the coverage of the Bi2O3 metal oxide protective layer and the sodium-loving Bi layer on the surface of the Al current collector.

[0046] Figures 4-6 The first-cycle charge-discharge curves of the half-cells of Comparative Example 1, Comparative Example 2, and Example 1 are shown, along with magnified first-cycle sodium deposition overpotential and voltage polarization diagrams. It is evident that the first-cycle coulombic efficiency of the half-cell of Comparative Example 1 is the lowest, while the first-cycle sodium deposition overpotential and voltage polarization are the highest, indicating the sodium affinity of the Al current collector and the significant irreversible sodium loss in the first cycle. In the first-cycle charge-discharge curves of the half-cells of Comparative Example 2 and Example 1, two reversible plateaus are observed at approximately 0.7 V and 0.5 V, corresponding to the formation and decomposition of NaBi and Na3Bi, respectively, demonstrating the reversibility of Bi-Na alloying. The first-cycle sodium deposition overpotential of the half-cell of Example 1 is slightly higher than that of Comparative Example 2, indicating a slight passivation effect of the Bi2O3 metal oxide protective layer. The lowest voltage polarization of the half-cell of Example 1 indicates that the presence of the Bi2O3 metal oxide protective layer effectively reduces polarization and promotes charge transfer kinetics. These data demonstrate that the present invention is feasible and can effectively reduce voltage polarization and promote uniform sodium ion deposition.

[0047] Figures 7-10The charge-discharge curves and long-cycle coulombic efficiency plots of the half-cells of Comparative Example 1, Comparative Example 2, and Example 1 at different cycle numbers are shown. It is evident that the half-cell of Comparative Example 1 short-circuited after 60 cycles. Although the half-cell of Comparative Example 2 could cycle up to 170 cycles before short-circuiting, the changes in the curves clearly show that the NaBi and Na3Bi plateaus gradually shortened and disappeared, indicating that the sodium-loving Bi layer gradually pulverized and deactivated due to drastic volume expansion. In contrast, the half-cell of Example 1 could stably cycle for 500 cycles with high curve consistency, the NaBi and Na3Bi plateaus remained intact, and the coulombic efficiency was stable, demonstrating the protective effect of the Bi2O3 metal oxide protective layer on the sodium-loving Bi layer. These data further prove the effectiveness and feasibility of the present invention, which has excellent effects in protecting the sodium-loving Bi layer, modulating uniform sodium ion deposition, and inhibiting sodium dendrite growth.

[0048] Figures 11-12 The first-cycle charge-discharge curves and long-cycle curves of the full cells of Comparative Example 1, Comparative Example 2, and Example 1 are shown. The Al / Bi / Bi2O3 composite current collector || sodium vanadium phosphate cathode full cell constructed in this invention (Example 1) has a first-cycle discharge specific capacity of 99.44 mAh·g. -1 After 60 cycles, it remained at 84.93 mAh·g -1 The first-cycle discharge specific capacities of the full cells in Comparative Example 1 and Comparative Example 2 were 74.72 and 93.99 mAh·g, respectively. -1 The comparative example 1 full cell had a discharge specific capacity of only 17.57 mAh·g after 26 cycles. -1 Comparative Example 2's full cell had a discharge specific capacity of 54.53 mAh·g after 60 cycles. -1 The above data demonstrate that the Bi₂O₃ metal oxide protective layer exhibits excellent protective effects on the sodium-loving Bi layer, effectively delaying its pulverization and deactivation, thereby improving the cycle stability of the full cell. These data fully reflect the important guiding role of this invention in the preparation of high-performance anode-free sodium metal batteries.

[0049] In summary, this invention abandons the traditional method of using a single sodium-loving metal layer. Instead, it generates Na2O through an in-situ reaction between a metal oxide protective layer and sodium ions, which participates in the formation of the SEI, thereby improving the stability of the SEI. This further promotes the uniform deposition / stripping behavior of sodium ions, inhibits sodium dendrite growth and interfacial side reactions, extends the service life of the sodium-loving metal layer, and significantly improves the discharge specific capacity, cycle stability, and cycle life of the anode-free sodium metal battery.

[0050] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A composite current collector, characterized in that: From bottom to top, a current collector substrate layer, a sodium-loving metal layer, and a metal oxide protective layer are sequentially arranged. The current collector substrate layer is made of at least one of copper foil, copper foam, carbon-coated copper foil, nickel foam, aluminum foil, aluminum foam, and carbon-coated aluminum foil, and the thickness of the current collector substrate layer is 1 nm to 1 cm. The sodium-loving metal layer is generally denoted by formula M, and the metal oxide protective layer is generally denoted by formula M. x O y M is one of the following: gold, silver, zinc, tin, antimony, bismuth, indium, magnesium, and calcium.

2. A method for preparing the composite current collector as described in claim 1, characterized in that: Specifically, the steps include the following: Step S1: Deposit a sodium-loving metal layer on the current collector substrate; Step S2: Deposit a metal oxide protective layer on the sodium-loving metal layer.

3. The method for preparing the composite current collector according to claim 2, characterized in that: In step S1, the deposition method of the sodium-loving metal layer is one or more of the following: direct coating, dry rolling, radio frequency magnetron sputtering, pulsed laser deposition, electron beam evaporation, molecular beam epitaxy, cluster beam deposition, evaporation deposition, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and plasma-enhanced physical vapor / chemical vapor / atomic layer deposition.

4. The method for preparing the composite current collector according to claim 3, characterized in that: The deposition method of the sodium-loving metal layer is as follows: radio frequency magnetron sputtering is used, with a metal M target as the precursor; a high-purity argon atmosphere is maintained; and the vacuum degree is 1×10⁻⁶. -2 ~1×10 -3 Pa; operating environment dew point is -60 ℃ to -30 ℃; deposition rate is 0.01 nm to 1 μm per minute; thickness of sodium-loving metal layer is 1 nm to 10 μm.

5. The method for preparing the composite current collector according to claim 2, characterized in that: In step S2, the deposition method of the metal oxide protective layer is one or more of the following: radio frequency magnetron sputtering, pulsed laser deposition, electron beam evaporation, molecular beam epitaxy, cluster beam deposition, evaporation deposition, physical vapor deposition, chemical vapor deposition, atomic layer deposition, and plasma-enhanced physical vapor / chemical vapor / atomic layer deposition.

6. The method for preparing the composite current collector according to claim 5, characterized in that: The specific deposition method for the metal oxide protective layer is as follows: radio frequency magnetron sputtering is used, with a metal M target as the precursor; the atmosphere is a mixture of argon and oxygen, with oxygen accounting for 10% to 90% by mass; the vacuum degree is 1×10⁻⁶. -2 ~1×10 -3 Pa; operating environment dew point is -60 ℃ to -30 ℃; deposition rate is 0.01 nm to 1 μm per minute; thickness of metal oxide protective layer is 1 nm to 10 μm.

7. A sodium metal battery without a negative electrode, characterized in that: It includes a positive electrode, a sodium battery electrolyte, a separator, and a composite current collector as described in claim 1.

8. The sodium metal battery without a negative electrode according to claim 7, characterized in that: The positive electrode includes a current collector and a positive electrode slurry disposed on the current collector, the positive electrode slurry containing a positive electrode material.

9. The sodium metal battery without a negative electrode according to claim 8, characterized in that: The current collector is made of copper foil or aluminum foil; the positive electrode material is at least one of positive electrode active material and positive electrode active material containing element doping, and the positive electrode active material is one or more of transition metal oxides, polyanionic compounds, and Prussian blue analogues.

10. The sodium metal battery without a negative electrode according to claim 9, characterized in that: The transition metal oxide is P2-Na. x Ni x Mn 1-x O2, O3-NaFe 1-x Mn x At least one of O2; the polyanionic compound is Na3V2(PO4)3 or Na2FeP2O7; the Prussian blue analogue is at least one of Na2Mn[Fe(CN)6] or Na2Fe[Fe(CN)6].